2015
DOI: 10.1039/c5mt00100e
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding spectrum and model structure of theBacillus anthracisvirulence determinant MntA

Abstract: The potentially lethal human pathogen Bacillus anthracis expresses a putative metal import system, MntBCA, which belongs to the large family of ABC transporters. MntBCA is essential for virulence of Bacillus anthracis: deletion of MntA, the system's substrate binding protein, yields a completely non-virulent strain. Here we determined the metal binding spectrum of MntA. In contrast to what can be inferred from growth complementation studies we find no evidence that MntA binds Fe(2+) or Fe(3+). Rather, MntA bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…At low intercellular concentrations of Mn(II), the mntABCD operons were assigned as the Mn(II) import system (Que and Helmann ). Our data indicate that despite Zn(II) and Mn(II) had similar binding affinities with MntA, Mn(II) is released much more readily than Zn(II), which is in accordance with a recent study, in which it was found that Zn(II) and Mn(II) bind differently to MntA in B. anthracis (Vigonsky et al ., ). Meanwhile, metal ion discrimination within the MntA is proposed to occur through subtle differences in the binding sites.…”
Section: Discussionmentioning
confidence: 97%
“…At low intercellular concentrations of Mn(II), the mntABCD operons were assigned as the Mn(II) import system (Que and Helmann ). Our data indicate that despite Zn(II) and Mn(II) had similar binding affinities with MntA, Mn(II) is released much more readily than Zn(II), which is in accordance with a recent study, in which it was found that Zn(II) and Mn(II) bind differently to MntA in B. anthracis (Vigonsky et al ., ). Meanwhile, metal ion discrimination within the MntA is proposed to occur through subtle differences in the binding sites.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesized that D-cysteine binds at the same site as Lcysteine or L-cystine, but that binding of Dcysteine induces a distinct conformational change that does not lead to increased thermostability. Recent studies have indeed demonstrated that binding of closely related substrates by SBPs can lead to different bound conformations (17,60,61). To explore this possibility, we conducted binding competition experiments using nanoDSF.…”
Section: Recognition Profile Of Fliy the Substrate Binding Protein (mentioning
confidence: 99%
“…They are involved in many important physiological processes such as nutrient import, cellular detoxification, lipid homeostasis, signal transduction, antiviral defense, and antigen presentation (5)(6)(7)(8)(9)(10)(11). From a clinical perspective, ABC transporters are of great interest as they are directly involved in tumor resistance to multiple chemotherapeutics, bacterial multidrug resistance, and bacterial virulence and pathogenesis (12)(13)(14)(15)(16)(17)(18)(19). All ABC transporters share a basic architecture, minimally composed of two intracellular nucleotide-binding domains (NBDs), and two trans-membrane domains (TMDs).…”
mentioning
confidence: 99%